Multicarrier Modulated Signal for Cognitive Radio with Low Peak-to-Average Power Ratio - Javaid A SHEIKH; Mehboob Ul AMIN; Shabir A PARRAH; G. Mohiuddin BHAT (International Journal of Applied Methods in Electronics and Computers, 2016)
Multi-carrier communication is considered as thepotential candidate for 4G-LTE networks. The major drawbackconcerned with multi-carrier communication is high PAPR,asvarious carriers are added via IFFT operation.High PAPR stillrequires a lot of attention due to non-linearity in poweramplifiers.In this paper we have generated a multi-carrier signalusing DVB-T2 parameters and calculated it PAPR using CCDF.A novel hybrid technique is proposed in which we have combinedthe filtering and companding techniques with SLM to obtain asignificant reduction in PAPR. The CCDF plots depict theperformance of proposed technique is better than existing art oftechniques.